Pengaruh Kompensasi, Budaya Organisasi, dan Motivasi terhadap Kinerja Karyawan PT. MBA - Febrina Fitriani; Denta Felli Ananda (Media Bisnis, 2023)
This study intends to analyze the effect of compensation, organizational culture, and motivation on employee performance at PT. MBA. In this study, a sample of 59 non-managerial employees was used with purposive sampling technique. Testing the hypothesis in this study using multiple linear regression analysis method. Based on the results of this study, it was concluded that there is an effect of compensation on the performance of employees of PT. MBA. Meanwhile, there is no influence between organizational culture and motivation on the performance of PT.MBA employees.